Gain enhancement of triple‐band patch antenna by using triple‐band artificial magnetic conductor. Issue 8 (26th March 2018) - Ghosh, Anumoy; Kumar, Vimlesh; Sen, Gobinda; Das, Santanu
Abstract : A microstrip line fed rectangular patch antenna with slots in the patch radiator is designed to realise triple resonant frequencies with satisfactory impedance matching (| S 11 |≤−10 dB) at 3.36, 5.96, and 9.09 GHz. Current distribution analysis is presented to provide an insight to the mechanism of triple resonance generation. A triple‐band artificial magnetic conductor (AMC) is designed and analysed based on resonance phenomenon of stepped impedance resonators. The resonant frequencies of the AMC coincide with the antenna. A rectangular split‐ring slot is embedded in the metallic ground of the antenna. The designed AMC is placed beneath the antenna maintaining an air gap between the structures. The slot in the ground plane enables the surface waves to interact with the AMC. The proposed arrangement enhances the gain from 1.38 to 3.77 dBi at 3.36 GHz, 3.22 to 6.29 dBi at 5.96 GHz, and 7.58 to 11.16 dBi at 9.09 GHz. The proposed structure exhibits good radiation patterns with low cross‐polarisation and high front to back ratio at all the three resonant frequencies. A prototype of the proposed structure is fabricated and the measured results are in good agreement with the simulated results.